Overcoming the time-bandwidth limit - Schulz, S.A.; Grassani, D.; Ivan, C.; Fabbri, S.J.; Upham, J.; Boyd, R.W.; K. L. Tsakmakidis; Brès, C.-S. (2018 British and Irish Conference on Optics and Photonics, BICOP 2018 - Proceedings, 2019)
We are so accustomed to the time-bandwidth limit that we often take it to be a fundamental relation that cannot be overcome. Contrary to this belief we here propose that the storage/delay time of a system can in fact be decoupled from the operating bandwidth, by breaking Lorentz reciprocity. We discuss two different mechanisms for breaking Lorentz reciprocity and show that - in the correct system layout - both can result in systems that exceed the conventional time bandwidth limit by orders of magnitude. © 2018 IEEE.